Modulated crystallization behavior, polymorphic crystalline structure and enzymatic degradation of poly(butylene adipate): Effects of layered metal phosphonate. (November 2015) - Chen, Yichun; Wang, Siyu; Chen, Qixian; Xi, Zhilin; Wang, Chenwan; Chen, Xiyi; Feng, Xin; Liang, Rong; Yang, Jinjun
Graphical abstract: Highlights: PPZn facilitates formation of PBA alpha-form due to crystal lattice matching. PPZn accelerates phase transition of PBA due to more energy available. PPZn hinders degradation of PBA due to epitaxial growth on surface of PPZn. Abstract: Layered metal phosphonate, zinc phenylphosphonate (PPZn) was synthesized and used as a model benign nucleating agent for poly(butylene adipate) (PBA) to manipulate the crystallization behavior, polymorphic crystalline structure and biodegradation of PBA. Upon incorporation of PPZn, the crystallization temperature ( T c ) and crystallinity of PBA increased. Meanwhile, the crystallization rate and spherulite density of PBA increased in the presence of PPZn, indicating that PPZn has an effective nucleating effect for PBA. PPZn is favorable for the formation of the PBA α -modification. Furthermore, PPZn would speed up highly the phase transition of PBA from the β - to α -one. PPZn significantly suppressed the biodegradation of PBA. Mechanisms for nucleating, preferential formation of the α -modification, accelerated phase transition and decreased degradation rate of PBA in the presence of PPZn have also been proposed. It is considered that layered metal phosphonate material is a new type of benign filler for controlling the polymorphic crystalline structure and biodegradation rate of the polymer, which is expected to further modify the property of the polymer and might widen the applications of biodegradable materials in the environmental and biomedical fields.